1998
DOI: 10.1046/j.1365-2141.1998.01077.x
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms of inherited factor V deficiency in 35 Iranian patients

Abstract: The type of bleeding symptom has been evaluated in 35 Iranian patients with an inherited deficiency of factor V, with plasma levels between 1% and 10%. The most frequent symptoms included epistaxis and excessive bleeding after surgery. Haemarthroses and muscle haematomas were less common, even in severely deficient patients. More severe symptoms such as gastrointestinal and central nervous system bleeding were rare. The severity of bleeding symptoms was only partially related to the degree of factor V deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
133
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(137 citation statements)
references
References 6 publications
(7 reference statements)
3
133
0
1
Order By: Relevance
“…However, its prevalence may be underestimated because mild cases are often overlooked [1,3,4]. This deficiency is due to an autonomic recessive transmission, it is more common in countries where consanguineous marriages are common, which is the case in our country.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…However, its prevalence may be underestimated because mild cases are often overlooked [1,3,4]. This deficiency is due to an autonomic recessive transmission, it is more common in countries where consanguineous marriages are common, which is the case in our country.…”
Section: Discussionmentioning
confidence: 92%
“…This deficiency is due to an autonomic recessive transmission, it is more common in countries where consanguineous marriages are common, which is the case in our country. Until now only 200 cases have been reported [3,5].…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms range from mucosal and post-traumatic bleeding, which are present in virtually all patients, to life-threatening intracranial and gastro-intestinal haemorrhages, which are rare and confined to the most severe cases (Lak et al, 1998;Huang & Koerper, 2008). As no FV concentrate is available, standard treatment relies on the administration of fresh frozen plasma (FFP).…”
mentioning
confidence: 99%
“…A clinically well-characterized cohort of 35 genetically unselected FV-deficient patients (Lak et al, 1998) served as a reference group. A literature search retrieved seven cases of FV deficiency attributable to homozygous splicing mutations, including the present report (Table I).…”
mentioning
confidence: 99%
“…165,166 Cases have been described of patients with factor V activity more than 0.1 iu/ml and severe bleeding, therefore, clinical history (for example, using the International Society on Thrombosis and Haemostasis bleeding assessment tool) 101 should be considered in addition to laboratory levels. Peyvandi et al 131 identified a factor V level for asymptomatic patients of 0.12 iu/ml (95% CI 0-0.34).…”
mentioning
confidence: 99%